Swearing in South Africa: Multidisciplinary research on language taboos (Journal of the Digital Humanities Association of Southern Africa, 2022)
Research on swearing (used here as a hypernym to include other phenomena and/or synonyms like cursing, profanity, taboo language, etc.) has been prevalent for many years internationally, also from a variety of scientific disciplines. Most of the research literature, however, is on swearing in English, although studies have also been conducted on some other languages. By contrast, very little to no research has been done on swearing within the South African context, which is quite surprising, given that using certain swearwords (i.e., racial slurs) is punishable by law. To address this void, we established a multidisciplinary project with its primary roots in the digital humanities, and with inputs from and implications to (amongst others) linguistics, literary studies, communication studies, neurology, psychology, sociology, computer sciences, and law. This project (and specifically the topic of swearing) holds the potential to provide insights in human cognition and social interaction, while situating it broadly within the scope of the Fourth Industrial Revolution. The project commenced in July 2019, and is currently ongoing.In this paper, we firstly provide a rationale for the project, before introducing each of the five subprojects. These subprojects pertain to swearing and the law; a swearing constructicon (a kind of online dictionary) for Afrikaans; swearing in the entertainment world and in the media; swearing as a linguistic innovation; and an end-user facing project website. We also report on some of the outputs from the project that are already available, and others that are still being developed and investigated. We conclude with a brief overview of some of the potential impacts of the project.
Keywords: censorship; computational linguistics; cursing; language change; taboo